An emulsion system derives from engkabang fat esters - Basri, Mahiran; Abd Gani, Siti Salwa; Abd. Rahman, Nur Fariza; Salleh, Abu Bakar; Abdul Rahman, Mohd Basyaruddin; Raja Abdul Rahman, Raja Noor Zaliha (2009)
An isotropic or homogeneous emulsion system comprises an oil phase including fat esters of illipe fat and a solubilizer; a non-ionic surfactants; and deionized water; characterized in that the solubilizer is a mixture of polyethyleneglycol-40 hydrogenated castor oil, polysorbate 20 and octoxynol-12.